SELF-ESTEEM DEVELOPMENT OF LILLIE’S CHARACTER IN THE POKÉMON SUN AND MOON VIDEO GAMES - Edo Edryananda; Singgih Daru Kuncara; Indah Sari Lubis (Fakultas Ilmu Budaya Universitas Mulawarman, 2020)
This study was conducted with the purposes to identify the self-esteem of Lillie in the Pokémon Sun and Moon video games as presented in the plot and the motives behind her self-esteem development. This study was based on qualitative research and used psychological approach. Therefore, this study focused on the psychological phenomenon of self-esteem. The data are the dialogues that convey Lillie’s self-esteem and the motives behind her self-esteem development. The data sources are Pokémon Sun and Moon video games and two other sources as data triangulation. The theories of self-esteem by Maslow and Branden were used to analyze the self-esteem of Lillie. The results of this study have shown that Lillie has low self-esteem in the exposition up to the rising action. Shortly after rising action starts, she has developed the high self-esteem. The Lillie’s high self-esteem remains up to the falling action and resolution. The first motive behind her low self-esteem development are the problems between she and her family. Lillie lost her family in the past. Secondly, it relates with her own self alone. She lacks of strength and has an unfavorable idea about Pokémon Trainer and Pokémon battle. These problems thwart her esteem desires and develop her low self-esteem. The motives behind her high self-esteem are related with her problems but resolved. She finds the supports from various characters along her journey. She gains independency and confidence. She fulfills her wish to save Nebby. Her thwarted desires are satisfied and her high self-esteem is developed then.